2012
DOI: 10.3382/ps.2011-01731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary oregano essential oil and vitamin E on the lipid oxidation stability of cooked chicken breast meat

Abstract: The antioxidant effect of oregano essential oil and vitamin E was evaluated in cooked chicken breast meat. In total, 480 broilers were randomly assigned to 6 treatments and 4 replications. Broilers were raised with a corn-soybean meal diet including either crude soybean oil or acidulated soybean oil soapstock, each supplemented with vitamin E at 10 or 100 mg or oregano essential oil at 100 mg/kg of feed. At 42 d, broilers were slaughtered and their breast meat was prepared into strips (1.5 × 10 cm) or patties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
1
22
0
3
Order By: Relevance
“…135 Supplementation with 0.1 g kg −1 oregano oil and vitamin E in chicken diets reduced lipid oxidation in meat when compared to the control, and the effectiveness of both antioxidants was similar. 160 In contrast, supplementation of swine diets with oregano oil did not promote an antioxidant effect on meat. 161 Cooked pork patties with olive leaf extract were produced with longissimus dorsi muscle from pigs reared under a diet supplemented with linseed oil, with results demonstrating that the dietary linseed oil increased ALA in meat, and the olive leaf extract reduced lipid and protein oxidation.…”
Section: Condiments Leaves Herbs and Spicesmentioning
confidence: 97%
See 1 more Smart Citation
“…135 Supplementation with 0.1 g kg −1 oregano oil and vitamin E in chicken diets reduced lipid oxidation in meat when compared to the control, and the effectiveness of both antioxidants was similar. 160 In contrast, supplementation of swine diets with oregano oil did not promote an antioxidant effect on meat. 161 Cooked pork patties with olive leaf extract were produced with longissimus dorsi muscle from pigs reared under a diet supplemented with linseed oil, with results demonstrating that the dietary linseed oil increased ALA in meat, and the olive leaf extract reduced lipid and protein oxidation.…”
Section: Condiments Leaves Herbs and Spicesmentioning
confidence: 97%
“…Beef, pork and poultry meat products Rojas and Brewer, 96 Sasse et al, 102 Rojas and Brewer, 128 Sacramlin et al, 159 Shan et al, 166 Trindade et al, 135 Sampaio et al, 186 Krishnan et al, 187 Avila-Ramos et al 160 …”
Section: Oreganomentioning
confidence: 99%
“…Only a few studies have reported no significant effects [97, 100103] or negative effects. For example, in the studies conducted by Goliomytis et al [98] and Marcinčák et al [104], who supplemented animal diets with quercetin and extracts of Camellia leaves, respectively, a decrease in productive performance, in terms of final body weight, feed intake and feed conversion, was observed.…”
Section: Growth Performancementioning
confidence: 99%
“…It has been well documented that using plant extracts rich in phenolic compounds could positively affect gut health and metabolism parameters of heat-challenged broilers (Akbarian et al, 2013). The positive effect of curcuma or its essential oil on the immunity of broilers has already been reported (Avila-Ramos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%